APPOINTMENT OF NORMAL TOLERANCES BY THE METHOD OF REFLECTIONS - Shilo, G. N.; Kovalenko, D. A.; Gaponenko, N. P. (Radio Electronics, Computer Science, Control, 2024)
Tolerance regions forming peculiarities under the normal distribution law and the external factors influence are being considered. An algorithm of a nominal tolerance assignment has been designed taking into account variations of elements parameters under external influences. The parameters tolerances calculations of active band-pass filter elements have been made.